Q: How do you solve 4x squared times 6x squared?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

-6x, -4x =

8x^2 + 6x - 5 = 8x^2 + 10x - 4x - 5 = 2x * (4x + 5) - (4x + 5) = (2x -1) * (4x + 5)

16x+9 without the rest of the equation, what this equals, I can't solve

-20=-4x-6x

4x2 + 5x + 1 - 4x2 - 6x = - x + 1 or 1 - x4x2 + 5x + 1 - 4x2 - 6x = - x + 1 or 1 - x4x2 + 5x + 1 - 4x2 - 6x = - x + 1 or 1 - x4x2 + 5x + 1 - 4x2 - 6x = - x + 1 or 1 - x

Related questions

-6x, -4x =

2x

4x-1 = 6x-15 4x-6x = 1-15 -2x = -14 x = 7

Add 4x + 2x = 6x + 4 = 6x + 4

-4x+3 = 23+6x -4x-6x = 23-3 -10x = 20 x = -2

If you mean: 4x+3 = 6x-9 then the value of x works out as 6

8x2 + 6x - 9 = 8x2 + 12x - 6x - 9 = 4x(2x + 3) - 3(2x + 3) = (2x + 3)(4x - 3)

(2x - 1)(6x + 5)

8x^2 + 6x - 5 = 8x^2 + 10x - 4x - 5 = 2x * (4x + 5) - (4x + 5) = (2x -1) * (4x + 5)

-20=-4x-6x -20=-10x {collect like terms} x=2 {divide each side by -10}

(4x - 3)(2x + 3)

4*x*x*6*x